Corrective Feedback Recast Uses in Students’ Uptake in Past Form Expressions - Theresia Arianti; Dery Rovino (Universitas Bunda Mulia, 2019)
Research studies have shown that recasts are one of the types of corrective feedback frequently used by teachers in second language teaching. However, little is known about the effectiveness of recasts in second language teaching within Indonesian context since most Interactional Approach studies conducted with Indonesian context focus on corrective feedback in general, not particularly on recasts. Moreover, most of these studies do not include past forms as the language feature being studied. The current study investigated the use of recasts in yielding students’ uptake in past forms (Verb type II). 5 participants were involved in the study. Pairing with the examiner, each participant engaged in a jigsaw-task activity where they received recasts. The recast episodes produced by each participant were analyzed and coded into some categories, which were “repair”, “needs-repair : acknowledgement”, “needs-repair : modified”, “needs-repair : unmodified”, and “no uptake”. The result showed that the uptake which was mostly produced by participants was “needs-repair : acknowledgement”. This finding contradicts the one in the previous study which showed that the uptake that was most frequently produced by the participants was “repair”. The finding of this study is expected to trigger further studies to examine students’ perception towards recasts that leads to the ineffectiveness of it.Keywords: corrective feedback; recast; past forms; speaking skills